Outward foreign direct investment and domestic output: evidence from East Asian economies - Morteza Kazemi,; W.N.W. Azman-Saini,; Naseem N.A.M, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study evaluates the impact of outward foreign direct investment (FDI) on domestic output of East Asian economies. It focuses on FDI from eight East Asian economies to Japan, the United States and United Kingdom. The analyses are carried out using annual data at both aggregate and disaggregate level for the 1981-2010 period. The result using aggregate data reveal that there is no evidence to support the idea that outward FDI is growth-enhancing. However, the results based on disaggregate data shows that only outward FDI to the United States are found to benefit East Asian economies. Meanwhile, investments in Japan and the United Kingdom do not appear to have any positive impact. These findings suggest that locational decision for outward FDI is critically important as not all destinations will bring positive benefits for the source countries.